Case report: Reversible Fanconi syndrome due to vitamin D deficiency in a patient with epilepsy harbouring a pathogenic variant in the SLC34A1 gene - Improda, Nicola; Rosanio, Francesco Maria; Annicchiarico Petruzzelli, Luigi; Ambrosio, Gyusy; Malgieri, Gabriele; Mandato, Claudia; Licenziati, Maria Rosaria (Frontiers in Endocrinology, 2025)
We report on a 3-year and 5-month-old boy who was referred for suspected rickets, due to knee valgus deformity developed over the previous year. The child had a history of epilepsy well-controlled with phenobarbital. His psychomotor development and growth metrics were appropriate for his age. On admission, laboratory work-up revealed elevated alkaline phosphatase (1289 U/L) and parathyroid hormone (PTH) (417 pg/ml), normal corrected calcium (9,3 mg/dl) and creatinine (0,21 mg/dl), low phosphate (3,2 mg/dl), 25-hydroxy vitamin D (6 ng/ml) and 1-25 hydroxy vitamin D (13.4 pg/mL, nv 20-80) concentrations. Urinalysis indicated low tubular reabsorption of phosphate (TRP % 10,7), along with bicarbonate, uric acid and amino acid loss, consistent with renal Fanconi syndrome. Based on these results, a genetic form of renal tubular dysfunction was suspected, and thus a clinical exome sequencing was requested. In the meanwhile, the child was commenced on Joulie solution (70 mg/kg/day of phosphate), calcitriol (0.03 mcg/kg/die), and ergocalciferol (1000 IU daily). FGF-23 concentrations were found to be within the normal range, thus ruling out FGF23-dependent forms of rickets. Surprisingly, we observed a dramatic improvement in laboratory parameters within two weeks from the treatment initiation, including normalisation of phosphate and PTH concentrations and resolution of Fanconi syndrome, prompting discontinuation of phosphate supplements. Molecular analysis identified a de novo monoallelic mutation (C.1006 + 1 G>A) in the solute carrier family 34 member 1(SLC34A1) gene encoding a protein involved in actively transporting phosphate into cells via Na+ cotransport in the renal brush border membrane. However, even without phosphate substitution no further drops in serum phosphate concentrations and persistently normal proximal renal tubular function were observed. Moreover the rickets changes had almost healed six months after starting vitamin D supplementation. This case provides further evidence that vitamin D deficiency may rarely cause renal Fanconi syndrome, reversible upon vitamin D replacement. This is particularly relevant in children with risk factors for vitamin D deficiency, including use of anticonvulsants.